Institutionalized Incentives for Ingenuity – Patent Value and the German Employees' Inventions Act - Dietmar Harhoff; Karin Hoisl (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
Germany is one of few countries in which the monetary compensation for inventors is not only determined by negotiations between employer and employee-inventor, but also by relatively precise legal provisions. In this paper, we describe the characteristics of the German Employees' Inventions Act (GEIA) and discuss which incentives it creates. We rely on responses from a recent survey of 3,350 German inventors to test hypotheses regarding this institution. We conclude from our data that the law creates substantial monetary rewards for productive inventors. The qualitative responses from our survey confirm this view, but also point to a number of dysfunctional effects.
urn:nbn:de:bvb:19-epub-1262-1
Keywords: O34; O32; J63; M54; 650; Employee-Inventor; Inventor Compensation; Patent Value; Productivity